Revisiting Apathy in Alzheimer’s Disease: From Conceptualization to Therapeutic Approaches - Antonio L. Teixeira; Mitzi M. Gonzales; Leonardo Cruz de Souza; Sara L. Weisenbach (Behavioural Neurology)
Apathy is a neurobehavioral syndrome characterized by impaired motivation for goal-directed behaviors and cognitive activity, alongside blunted affect. Apathy is a common neuropsychiatric syndrome in Alzheimer’s disease (AD), with a 5-year prevalence over 70%. Apathy also serves as a prognostic indicator, correlating with the progression of AD. Despite advances in its conceptualization and understanding of its neural basis, there is very limited empirical evidence to support the available strategies for the treatment of apathy in AD. Given its complex pathophysiology, including distinct substrates for different apathy dimensions (affective, cognitive, and behavioral), it is unlikely that a single pharmacological or nonpharmacological strategy will be effective for all cases of apathy in AD. High-quality evidence research is needed to better understand the role of specific strategies aiming at a personalized approach.